Otentikasi Digital Hadis: Penerapan Kecerdasan Buatan dalam Analisis Isnād dan Matn serta Penerapannya dalam Hukum Islam - Ingah Maulana; Muhammad Faisal Hamdani; Mhd. Syahnan; Asmuni (Jurnal Ragam Pengabdian, 2026)
The rapid development of digital technology and artificial intelligence (AI) has created new opportunities to strengthen the methodology of ḥ.adīth studies, particularly in the process of authentication, which has traditionally relied on qualitative classical approaches. This study aims to examine the application of artificial intelligence in the digital authentication of ḥ.adīth through the analysis of isnād and matn, as well as to assess its implications for the legal authority of ḥ.adīth in Islamic law. This research is motivated by the need for a more systematic, objective, and replicable method of ḥ.adīth verification without disregarding the established principles of classical ḥ.adīth sciences. The study employs a qualitative-descriptive approach reinforced by a quantitative– computational model, integrating rijāl al-ḥ.adīth analysis, verification of sanad continuity, and natural language processing (NLP) techniques to evaluate the semantic consistency and textual reliability of ḥ.adīth matn. A case study is conducted on the ḥ.adīth prohibiting the exchange of gold for gold and silver for silver except on an equal and immediate basis. The findings indicate that AI-based analysis is able to accurately confirm the authenticity of the isnād by validating the credibility of transmitters and the continuity of transmission, as well as to assess the validity of the matn through its consistency with the Qur’an and other authentic ḥ.adīths. The integrated analysis of isnād and matn confirms that the examined ḥ.adīth qualifies as ṣ.aḥ.īḥ. li dhātih and possesses full legal authority in Islamic law. This study concludes that artificial intelligence serves as an effective epistemological tool to strengthen ḥ.adīth authentication and holds significant potential for development as a decision-support system for contemporary Islamic legal reasoning.